2002
DOI: 10.1182/blood-2002-01-0235
|View full text |Cite
|
Sign up to set email alerts
|

Donor-lymphocyte infusion induces transplantation tolerance by activating systemic and graft-infiltrating double-negative regulatory T cells

Abstract: Donor-lymphocyte infusion (DLI) before transplantation can lead to specific tolerance to allografts in mice, nonhuman primates, and humans. We and others have demonstrated a role for regulatory T cells in DLI-induced, donor-specific transplantation tolerance, but it is not known how regulatory T cells are activated and where they execute their function. In this study, we observed, in both transgenic and normal mice, that DLI before transplantation is required for activation of ␣␤-T-cell-receptor-positive, CD3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 61 publications
7
91
0
Order By: Relevance
“…In recent studies, we found that TCRab + CD3 + CD4 -CD8 -(double-negative, DN) T cells possess immuneregulatory functions and play an important role in the development of tolerance post-transplantation [22][23][24][25]. We have demonstrated that mouse DN-Treg specifically can eliminate activated syngeneic anti-donor CD4 + T cells, CD8 + T cells, and B cells [22,23,25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, we found that TCRab + CD3 + CD4 -CD8 -(double-negative, DN) T cells possess immuneregulatory functions and play an important role in the development of tolerance post-transplantation [22][23][24][25]. We have demonstrated that mouse DN-Treg specifically can eliminate activated syngeneic anti-donor CD4 + T cells, CD8 + T cells, and B cells [22,23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This notion has been well addressed in the hybrid resistance model, in which parental BM cells, not solid organs, are vigorously rejected by an F1 hybrid [10,11]. This rejection is mediated solely by a recipient's NK cells, not by T cells, NKT cells or B cells [12][13][14] [20,21].In recent studies, we found that TCRab + CD3 + CD4 -CD8 -(double-negative, DN) T cells possess immuneregulatory functions and play an important role in the development of tolerance post-transplantation [22][23][24][25]. We have demonstrated that mouse DN-Treg specifically can eliminate activated syngeneic anti-donor CD4 + T cells, CD8 + T cells, and B cells [22,23,25,26].…”
mentioning
confidence: 99%
“…We have previously shown that DN Treg cells preferentially accumulate in accepted skin allografts (28). Furthermore, DN Treg clones, but not mutant clones, are able to migrate to cardiac allografts and induce tolerance.…”
Section: -Fold Higher By Qrt-pcr)mentioning
confidence: 99%
“…We and others (15,17,27,28) have previously demonstrated that DN Treg cells isolated from tolerant animals can inhibit the function of syngeneic CD8 ϩ and CD4 ϩ T cells, which is at least partially due to direct killing of activated CD4 or CD8 T cells. To examine the in vitro functional differences between regulatory DN Treg clones and their mutant progeny, preactivated CD8 ϩ T cells were cocultured with increasing numbers of either regulatory clones (CN4 and TN12) or mutant clones (CN4.8 and TN12.8).…”
Section: Generation and Characterization Of Dn Treg And Mutant Clonesmentioning
confidence: 99%
See 1 more Smart Citation